O-068 Training of clinicians: How to do it and how to best evaluate it. (6th August 2021) - Feki, A; Tatjana, M; Roy, F
Abstract: Training of clinicians: How to do it and how to best evaluate it? Anis Feki, Tatjana Motrenko, Roy Farquharson Many countries within Europe and EU do not have a specific national agency that provides the necessary structure or governance for appropriate training in Reproductive Medicine (RM). Therefore, The European Society of Human Reproduction and Embryology (ESHRE) has been the responsible agency for accreditation of RM training alongside its sister organization, the European Board and College of Obstetrics and Gynaecology (EBCOG). Both of these organizations are ultimately responsible to and approved by the Union of European Medical Specialties (UEMS), which represents the European Union (EU) governing body for medical practitioners' education. The Reproductive Medicine subspecialist is a specialist in basic obstetrics and gynecology who has undergone theoretical and practical training in the medical and surgical management of infertility, including assisted reproductive techniques (ART). In general, the comprehensive management of these problems includes both diagnostic and therapeutic procedures allied to continuous audit of outcome. The global aim is to improve the care of patients with disorders of reproductive function. To reach this target, both ESHRE and EBCOG put in place a program that starts with accreditation of training centers in obstetrics and gynecology and more specifically, specialist training centers in reproductive medicine. Fellows must have a structured program of a minimum of 2 years after completing their basic obstetrics and gynecology syllabus and/or obtaining EFOG European Fellow of Obstetrics and Gynecology) diploma for non-European basic training. When a training fellow in RM has completed their logbook, the fellow will finish by assessing an individual's knowledge and skills by passing an exit-training exam called the EFRM (ESHRE-EBCOG Fellow in Reproductive Medicine) diploma. The success of and the need for such certification has led ESHRE to structure the training also for reproductive surgeons, embryologists, as well as nurses and midwives. In addition, several countries within the EU already have a national compulsory specialist accreditation system for RM training. Recent proposals by the EU Commission to build European reference networks across all specialties, including RM may require the recognition of ESHRE/EBCOG–accreditation as an appropriate entry point for consideration of diagnostic and other interventions. Encouraging subspecialists and centers to apply for training accreditation may well prove to be an increasingly attractive option as educational needs across Europe become integrated and formalized through UEMS. ESHRE holds the view that accredited centers/subspecialists for training are beacons of excellence that often go hand in hand with high-quality research.